РОЗВИТОК У ШКОЛЬНИКІВ КОМПЕТЕНЦІЇ ЗАСОБАМИ ТЕСТУВАННЯ (Педагогіка вищої та середньої школи, 2004)
The author defines the notion of competence and analyses ways of developing student's competence. The advantages of test teaching technologies are examined.